Do Obstetricians Apply the National Guidelines? A Vignette-based Study Assessing Practices for the Prevention of Preterm Birth. Issue 4 (December 2020) - Rousseau, A.; Azria, E.; Baumann, S.; Deneux-Tharaux, C.; Senate, M.V.
Abstract : ( BJOG . 2020;127:467–476) While clinical guidelines are developed by synthesizing scientific evidence with the intent to assist clinicians' in decision-making, studies show generally low levels of adherence to those guidelines, especially in obstetrics. This may be in part to inadequate dissemination of guidelines. International guidelines for the management of spontaneous preterm birth have been recently issued, yet management practices continue to vary widely. This study aimed to describe clinician practices for preventing spontaneous preterm birth before and following guideline issuance and identify factors that may affect adherence to guidelines.